2019
DOI: 10.1021/acsearthspacechem.9b00134
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Titanium Dioxide (TiO2) in the Production of Perchlorate (ClO4) from Chlorite (ClO2) and Chlorate (ClO3) on Earth and Mars

Abstract: The widespread presence of perchlorate (ClO 4 − ) on Mars has significant implications for the alteration or destruction of indigenous organic compounds that may have been or still be present on Mars. The intermediary products of the UV-driven production of ClO 4 − include oxychlorines (ClO x ) such as chlorite (ClO 2 − ), chlorate (ClO 3 − ), and chlorine-dioxide (ClO 2 ) gas. The objective of this study was to start with ClO 2 − or ClO 3 − under Mars ambient and vary temperature, humidity, and UV wavelengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Laboratory experiments demonstrated that perchlorate production is possible via aqueous‐phase oxidation of Cl x O y species or gas‐solid‐plasma interactions (Carrier & Kounaves, 2015; Dasgupta et al., 2005; Estrada et al., 2021; Jackson et al., 2018; Kang et al., 2006, 2008, 2009; D. Liu & Kounaves, 2019; Rao, Mohan, et al., 2012; Wu et al., 2018). Some of these reactions could potentially occur on aerosols, in clouds, and/or land surfaces.…”
Section: Hypotheses For Explaining Discrepancies Between Observations...mentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory experiments demonstrated that perchlorate production is possible via aqueous‐phase oxidation of Cl x O y species or gas‐solid‐plasma interactions (Carrier & Kounaves, 2015; Dasgupta et al., 2005; Estrada et al., 2021; Jackson et al., 2018; Kang et al., 2006, 2008, 2009; D. Liu & Kounaves, 2019; Rao, Mohan, et al., 2012; Wu et al., 2018). Some of these reactions could potentially occur on aerosols, in clouds, and/or land surfaces.…”
Section: Hypotheses For Explaining Discrepancies Between Observations...mentioning
confidence: 99%
“…Oxygen isotopes suggest that atmospheric ozone (O 3 ) is involved in the formation of perchlorate sampled from the Atacama desert of Chile and Death Valley in the US (Bao & Gu, 2004; Jackson et al., 2010). Laboratory experiments have studied various perchlorate‐production mechanisms, such as aqueous reaction of oxychlorine (Cl x O y ) in the presence of ozone and/or UV light (Dasgupta et al., 2005; Estrada et al., 2021; Kang et al., 2006, 2008, 2009), solid‐gas interactions between chloride and ozone (Estrada et al., 2021; Jackson et al., 2018; Kang et al., 2008), photo‐catalyzed electrochemistry (Carrier & Kounaves, 2015; D. Liu & Kounaves, 2019), and plasma chemistry during electric discharge (Dasgupta et al., 2005; Rao, Mohan, et al., 2012; Wu et al., 2018). However, the contribution of these mechanisms to the occurrence of non‐synthetic perchlorate on Earth remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…A 0.5 g sample was placed in each vial during the experiment with a resulting sample layer thickness of ~ 1 mm. The samples were configured as previously described (Liu and Kounaves, 2019).…”
Section: Sample Preparationmentioning
confidence: 99%
“…During this process several oxychlorine intermediates such as hypochlorite (ClO -), chlorite (ClO 2 -), chlorate (ClO 3 -), and chlorine dioxide (ClO 2 ) gas, as well as radicals such as • OCl, • Cl, O 2and • OH are also likely generated (Catling et al, 2010). Recently, it was confirmed that the photochemical perchlorate formation pathway can exist without ozone (O 3 ) and that a highly oxidizing oxychlorine gaseous intermediate, most likely ClO 2 gas, was present in this pathway (Liu and Kounaves, 2019;Jain et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to explain the presence of ClO 4 – on Mars include hypotheses involving atmospheric reactions between oxidants such as ozone and volatile chlorine (Cl) species , or gas–solid phase reactions involving ozone and Cl-bearing minerals. As an alternative to these hypotheses, two studies , have demonstrated that ClO 4 – and other oxychlorines such as chlorate (ClO 3 – ) and chlorite (ClO 2 – ) can be photochemically produced and degraded in the presence of illuminated semiconducting minerals (e.g., anatase and rutile) under Earth- and Mars-like conditions.…”
Section: Introductionmentioning
confidence: 99%